New records of tardigrades from Colombia with the description of Paramacrobiotus sagani sp. nov. and Doryphoribius rosanae sp. nov. - Daza, Anisbeth; Caicedo, Martín; Lisi, Oscar; Quiroga, Sigmer (Zootaxa, 2017)
By examining material collected in the Sierra Nevada de Santa Marta (Department of Magdalena, Colombia), the authors report a new record for the entire South America, Doryphoribius gibber Beasley & Pilato, 1987, and two species new to science, Paramacrobiotus sagani sp. nov., and Doryphoribius rosane sp. nov., are described. Paramacrobiotus sagani sp. nov. belongs to the richtersi group, vanescens subgroup (by having sculptured egg areolae) and is characterized by a peculiar cuticular granulation, trunco-conical egg processes with cylindrical indented apices, and other more detailed cha-racters both qualitative and metric; by the unique combination of characters, it differs from all the other known species of the genus. Doryphoribius rosanae sp. nov. is characterized by reticulated dorsal cuticle with gibbosities (formula IX:4-6-2-6-2-6-4-2-2), two macroplacoids in the pharynx without microplacoid or septulum, and large, stout claws without “free” accessory points but with lunules. It differs from all the other Doryphoribius species with gibbosities by having a unique formula, as well as other more detailed characters. Thanks to this contribution, the number of tardigrade species known for Colombia increases from 52 to 55.